HIV alters the expression of miRNA hsa-miR-200c-3p in B-cells, leading to enhanced migration of lymphoma cells - Ramorola, Beatrice Relebogile (Department of Pathology, 2019)
Background: The sub-Saharan African region is one that is affected most by the HIV/AIDS pandemic, with South Africa being the country with the highest number of infected individuals at 7.06 million. Infection with HIV is often associated with co-morbidities, including HIV-associated Non-Hodgkin’s Lymphomas (HIV-NHLs). Burkitt’s lymphoma (BL), a highly aggressive cancer, is one of the most common NHLs associated with HIV infection. Despite receiving highly active anti-retroviral therapy, the prognosis for this HIV-associated lymphoma remains poor and the incidence keeps on increasing in this group of patients. Recent studies have shown that microRNA (miRNA) dysregulation play essential roles in the pathogenesis of many cancers, including NHLs. While several human pathogenic viruses have been shown to deregulate cellular miRNAs, to date, no comprehensive studies have been carried out to determine whether HIV infection can lead to miRNA dysregulation in B-cells, which may contribute to the development of HIV-associated lymphomas. Objective: This research project aimed to validate the differential expression of selected miRNAs which were identified as potentially important in a PCR array, and characterise their roles in Burkitt’s lymphoma cells exposed to an attenuated strain of HIV-1, compared to control cells. Methods: Single-tube TaqMan miRNA assays were used to validate the previously observed differential expression of four selected miRNAs in Burkitt’s lymphoma cell lines (Ramos and BL41) exposed to HIV-1 compared to matched-microvesicle treated (control) cells. Following validation, the role of miRNA hsa-miR-200c-3p in the development of HIV-associated BL was investigated. This was done by using online bioinformatic prediction tools, as well as literature searches, to identify gene targets. Thereafter, the differential expression of a selected gene target was investigated by qPCR and western blotting. The functional significance of the observed changes in miRNA and gene expression was investigated by performing cell viability and migration assays. Results: Three upregulated (hsa-miR-575, hsa-miR-363-3p and hsa-miR-222-3p) and one downregulated (hsa-miR-200c-3p) miRNAs that were significantly deregulated by 2-fold or more (p< 0.05) in the PCR array were selected for validation. Thereafter, the miRNA hsa-miR200c-3p was selected for further analysis. Upon exposure to attenuated HIV-1, hsa-miR-200c3p was downregulated in the BL cell line Ramos, and this was reproducible in a second BL cell line BL41. The transcription factors ZEB1 and ZEB2, which are involved in cancer cell migration, were identified as targets of hsa-miR-200c-3p. Contrary to what is expected, the mRNA expression of both genes was found to be significantly downregulated in Ramos and BL41 exposed to attenuated HIV-1. At the protein level, in the Ramos cells, ZEB1 and ZEB2 matched what was observed for the mRNA. In contrast, both ZEB1 and ZEB2 protein were upregulated in BL41 cells under the same treatment conditions. At the functional level, the migration of both cell lines was enhanced when exposed to attenuated HIV-1, compared to control cells. Conclusions: The present study has demonstrated that HIV-1 has the ability to modulate cellular miRNA expression in Burkitt’s lymphoma cells. Of these miRNAs, hsa-miR-200c-3p is consistently downregulated when two BL cell lines were exposed to HIV. The ZEB transcription factors ZEB1 and ZEB2, which promote Epithelial-to-Mesenchymal Transition (EMT) through enhancing cellular migration, were investigated as hsa-miR-200c-3p targets. The mRNA levels of ZEB1 and ZEB2 were downregulated in both cell lines under the same experimental conditions. This is contrary to what is expected, since miRNAs lead to the attenuation of transcription or translation of their target genes and a downregulation of a miRNA should lead to an upregulation of its target. However, protein expression rather than mRNA expression has been described as a more accurate indication of target validation for miRNAs. The protein expression levels for ZEB1 and ZEB2 correlated with the mRNA expression results observed in the Ramos cells. In the BL41 cells, ZEB1 and ZEB2 protein levels were upregulated. Furthermore, in both cell lines, an increase in migratory ability was observed when cells were exposed to attenuated HIV-1. These results demonstrate that exposure to HIV enhances the cancer phenotype and that this is potentially due to changes in cellular miRNA expression brought about by the virus or viral components. Future studies should focus on gain-offunction and loss-of-function studies to determine whether the increase in cell migration is specifically due to a decrease in hsa-miR-200c-3p.